Pengaruh Kedisiplinan, Motivasi Dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada PT. BFI, TBK. Sragen - Wicaksana, Oryza; , Edy Purwo Saputro, SE. M.Si (2017)
This study aims to determine how the effect of the performance of employees at PT. BFI, Tbk Sragen measured by using three (3) variables: variable discipline, motivation variable and variable work environment. The method used was survey method with data collection in the form of a questionnaire (questionnaire), this research further including explanatory research design. Sampling technique is done by total sampling taken as many as 40 people, which amount is the total number of employees at the BFI office, Tbk Sragen. While data analysis using qualitative analysis and quantitative analysis. From the data processing as many as 40 respondents about the influence of discipline, motivation and work environment to employees performance of PT. BFI, Tbk Sragen: first there is significant influence between work discipline on the performance of employees of PT. BFI, Tbk Sragen. Secondly there is significant influence between work motivation on employee performance PT. BFI, Tbk Sragen. And thirdly there is significant influence between the work environment on the performance of employees of PT. BFI, Tbk Sragen.